-P.i.c. − functors in the category of Tych Tikhonov spaces and continuous mappings into themselves and dimension dim. - Gulchekhra Mukhamedova; Feruza Saydalieva; Dilnoza Ibragimova; Kamariddin Zhuvonov; Tursunboy Zhuraev (The Bioscan, 2024)
This note studies the geometric, topological and dimensional properties of the. .p i c  − -functor and its subfunctors in the category ofTych − Tychonov spaces and continuous self-maps.